Identification and Mechanistic Studies of Key Genes in Thalamic Hemorrhage Pain by Multi-omics - Chen Yang; Ju Gao; Yaqun Li; Yinggang Xiao; Tianfeng Huang (Journal of Integrative Neuroscience)
Background: Thalamic hemorrhage pain (THP), a subtype of central post-stroke pain (CPSP), commonly develops following ischemic or hemorrhagic injury to the thalamus. Current therapeutic options remain inadequate due to the absence of well-defined molecular targets. This study aimed to elucidate critical genes implicated in THP pathogenesis through an integrated multi-omics approach. Methods: A mouse model of THP was established and mice were divided into THP and control groups. Comprehensive multi-omics profiling involving transcriptomics, proteomics, metabolomics, ribosome profiling (Ribo-seq), and single-cell RNA sequencing (scRNA-seq) was conducted. Differentially expressed genes (DEGs), differentially expressed proteins (DEPs), ribosome footprint-associated DEGs (RF-DEGs), and differentially expressed metabolites (DEMs) were identified via comparative expression analyses. Hub genes were extracted from the DEGs and subsequently intersected with scRNA-seq DEGs, DEPs, and RF-DEGs to define key gene candidates. These genes underwent gene set enrichment analysis (GSEA), disease association mapping, and drug prediction. Expression levels of key genes were used to delineate critical cell populations, followed by analyses of intercellular communication and pseudotemporal differentiation trajectories. Orthogonal partial least squares discriminant analysis was used to validate the model. Results: The THP mouse model was successfully validated. Multi-omics analyses yielded distinct profiles of DEGs, single-cell DEGs, DEPs, RF-DEGs, and DEMs, which were functionally annotated through enrichment strategies. Notably, 12 hub genes were prioritized, of which eight key genes (ferritin light chain 1 (Ftl1), tropomyosin 4 (Tpm4), C-C motif chemokine ligand 3 (Ccl3), C-C motif chemokine ligand 4 (Ccl4), C-C motif chemokine receptor 2 (Ccr2), interleukin 33 (Il33), C-X-C motif chemokine ligand 2 (Cxcl2), and Lymphocyte antigen 6 complex, locus C2 (Ly6c2) were identified. These genes were predominantly associated with oxidative phosphorylation and ribosomal pathways. Further analyses revealed strong associations with necrotic and inflammatory processes, and compounds such as alprostadil and anisomycin were identified as potential therapeutic agents. Single-cell analyses highlighted six pivotal cell types, including endothelial cells and macrophages. Intercellular communication networks and lineage progression patterns of these cells were systematically characterized, alongside spatial and temporal expression profiles of key genes. Conclusions: This study established a validated THP mouse model and employed a multi-omics integration strategy to identify eight key genes and associated molecular pathways. These findings provide novel mechanistic insights into THP pathogenesis and highlight promising targets for therapeutic intervention.